Features of the organization of medical psychological care in oncological practice at different stages of treatment - Kliusov Олександр; Kontdratenko Андрій; Kalachov Олексій; Mukharovska Інна (Psychosomatic Medicine and General Practice, 2021)
This text is the thesis of the III scientific-practical conference with international participation "Psychosomatic medicine: science and practice". The following is devoted to the features of the organization of medical psychological care in oncological practice at different stages of treatment.